(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
An investigation was conducted to have a clear idea on current aquaculture practicesof 67 fish farmers in Birganjupazila, Dinajpur district for a period of six months fromOctober 2016- March 2017. Fish farmers were selected randomly from three villagesof Moricha Union of Birganjupazila through questionnaire interview, FGD and crosscheck interview and secondary information were used to assess the performances inaquaculture activities. Most of the farmers (52.24%) had pond having the size rangefrom 5 to10 decimal with the mean depth 4.44 ft. It was found that 79% of pondscontained water throughout the year and 21% pond had water for a period of 6 to 8months. The major culture species was Indian major carps along with SmallIndigenous Species. About 76% farmer used feed in culture pond and none of thefarmers were found to take any measures for maintaining proper water quality. Thetotal fish production was found as 1204 kg where Tilapia ranked highest with 22% inthe study area. About 92.5 % farmers use the fish only for family consumptionwhereas the remaining farmers (7.5%) used for both family consumption and sales.The major problems identified during the culture period were high price of quality fishseeds and feeds, less protein in feed, poor technical knowledge etc. It is therefore,necessary to provide necessary training to the farmers, institutional and policysupports and proper credit facilities for sustainable fish production as well assustainable livelihood of the poor farmers. Res. Agric., Livest. Fish.7(2): 341-349, August 2020